To determine the customer satisfaction factor to architecture design of Malaysia high rise residential building projects during the design and planning stage / Lo Jia Woei - Lo, Jia Woei (2022)
Customer satisfaction in high-rise residential buildings has evolved as an influential framework in psychology, personal life satisfaction, community lifestyle, health, and well-being. Architectural design has played a vital part in influencing the state and is the main aspect that will directly influence house buyer decisions in Malaysia. This study aims to determine the significant customer satisfaction element in high-rise residential architectural design based on the unit layout plan and project design. Furthermore, this study has specified the function of a professional architect in supervising and ensuring the quality of high-rise residential architectural design. This study employed a mixedmethod approach, with quantitative data serving as the primary source of information. Structured interviews were conducted to validate the customer satisfaction factor in Malaysian high-rise residential buildings based on questionnaire findings. The results of the interviews were utilized to determine if the customer satisfaction factor was equivalent to a professional architect's high-rise residential building design requirements. A total of 189 questionnaires were sent to the intended house buyer at one of Malaysia's high-rise residential complexes. Seventy people responded, and their responses were determined to be beneficial for data analysis. Three of the project architects mentioned above were interviewed for the construction project. The data were analyzed using the Statistical Package for the Social Sciences (SPSS). From the data analysis, thirteen (13) primary factors in architectural design significantly affect customer satisfaction. They are House floor plan design; Quality of finishes IV workmanship; Quality of materials used for floor and wall; Unit scale and proportion; Size of the rooms in the unit; Brightness or light in the unit during daytime; Location of different rooms; Safety and security; Building accessibility; Building durability and life span; Building orientation; Facility plan design and usage; Building performance requirements. While four (4) primary roles in terms of professional architect services to significantly affect customer satisfaction are Managing defects on architectural work; Project design control; Supervision skill on construction work, and Quality assurance on building work. According to the interview results, there is some disagreement between the customer satisfaction factor and the architect's point of view. Based on the data, it is possible to infer that the architectural design and services supplied by the architect in the high-rise residential impact customer satisfaction. As a result, greater emphasis is likely to be placed on those characteristics to increase consumer satisfaction with Malaysia's high-rise residential building architectural design.